DETERMINANTS OF MORTALITY AND DISEASE SEVERITY IN EMERGENCY VENTRAL HERNIA REPAIR: A PROSPECTIVE STUDY FROM A TERTIARY CARE CENTRE - Dr Preethika M; Dr Magesh C; Dr. Madan S; Dr Ajay Gokul; Dr Kuberan k (The Bioscan, 2026)
Background: Emergency ventral hernia repair carries significantly higher morbidity and mortality than elective surgery, largely due to delayed presentation and bowel compromise. However, prospective data identifying determinants of mortality and operative decision-making in such settings remain limited. Materials and Methods: This prospective observational study included 50 patients undergoing emergency surgery for complicated ventral hernia (2024–2026). Clinical, intraoperative, and postoperative variables were analysed. Logistic regression identified independent predictors of mortality. Results: Most patients were aged 51–70 years (62%). Strangulation occurred in 38%, and bowel resection was required in 34%. Postoperative complications occurred in 58%, with overall mortality of 22%. All deaths occurred in patients with strangulation requiring bowel resection and postoperative sepsis. Mortality among resection cases was 64.7%. Strangulation (OR 6.8, p = 0.002), bowel resection (OR 9.4, p < 0.001), and age >60 years (OR 2.6, p = 0.04) were independent predictors of mortality. Type of repair was not associated with complications (p = 0.66). Conclusion: Mortality in emergency ventral hernia is primarily driven by disease severity at presentation rather than operative technique. The progression from delayed presentation to strangulation and bowel resection represents a critical pathway leading to adverse outcomes. Early elective repair and timely intervention are essential to reduce mortality.